Design and 3D-printing of a rinsing chamber for hydrostatic high-pressure treated allogeneic tissues (Transactions on Additive Manufacturing Meets Medicine, 2021)
Nowadays, the use of additive manufacturing processes is widespread in the area of medical applications due to the advantages such as the wide variety of materials and the flexibility regarding the unique or single-part production to fabricate, for example, implants, surgical devices and guides as well as prostheses. As part of a joint project, our research groups have developed a rinsing system for allogeneic tissues and printed all relevant components by using stereolithography. The results presented in this scientific work show the use of this technology to fabricate biocompatible and steam sterilizable chambers and tissue holders for the rinsing system.
Keywords: stereolithography; rinsing chamber; allograft; biocompatible; steam sterilizable